Análise da influência do tempo de armazenamento na estabilidade físico-química e microbiológica de matrizes homeopáticas de uma farmácia de manipulação de Maceió-AL - Voss, João Paulo Toledo (2015)
This study evaluates the influence of storage time on the physicochemical and microbiological stability in homeopathic matrices. Has the purpose then ponder the real validity of these matrices, whereas the same can only be evaluated on these matters due to the characteristics of infinitesimal dilutions where the chemical composition is related to the vehicle and not the solution. In evaluating the physical and chemical stability, were applied three methods of analysis relating to the determination of the alcohol content, the latter being the pharmacopeial method of relative density as the reference method and two non pharmacopoeia complementary methods: gas chromatography (GC) and differential scanning calorimetry (DSC). For the evaluation of microbiological stability, culture of microorganisms was held on board, two different methods employed, as described in the United States Pharmacopeia and accepted by the Brazilian Pharmacopoeia, currently in force, and a complementary method of not pharmacopoeia origin. Through this study it was observed that the physico-chemical, ethanol whose securities must maintain the same or higher levels to 77% v/v or 70% m/m, did not obtain consistent values, due to an error in the production process of matrices, it was not possible inferences as to the physical and chemical stability. About the microbiological testing of homeopathic matrices, it is observed that these being stored properly, the microbiological integrity is retained for a period of 25 years, a fact denoted by the absence of growth of mesophilic microorganisms or growth within the limits accepted by Brazilian Pharmacopoeia and through the observation of absence of pathogens.